PERAN MEDIASI MOTIVASI DALAM PENGARUH TUNJANGAN KINERJA DAN KEPEMIMPINAN TERHADAP PRODUKTIVITAS (STUDI PADA PEGAWAI KOMISI PEMILIHAN UMUM KABUPATEN/KOTA SE-PULAU LOMBOK) - zinnurain zinnurain; thatok Asmony; hermanto hermanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This study aims to determine the effect of performance benefits to the motivation and leadership, and leadership performance benefits to productivity, motivation effect on productivity, the impact on the productivity performance benefits through the mediation of motivation, as well as the influence of leadership on productivity through mediation motivation. The survey respondents are all civil servants Regency / City Lombok island numbered 97 people. But filling questionnaire answers just as much as 87 people. Data analysis techniques in this study conducted by SmartPLS 3..0. As a result, the leadership performance benefits and positive and significant impact on the motivation; allowances and leadership performance and no significant positive effect on productivity; motivation positive and significant effect on productivity; performance benefits positive and significant impact on productivity through the mediation of motivation; leadership and significant positive effect on productivity through mediation motivation.Keywords: performance benefits, leadership, motivation and productivity